Investigating EFL Students’ Difficulties in Producing English Interdental Fricatives (/Θ/ and /Ð/): A Descriptive Quantitative Study - Putri Nurmeiga Amaliarrafiun; Hastini; Maf’ulah Maf’ulah; Zarkiani (FOSTER: Journal of English Language Teaching, 2026)
This study investigates the pronunciation difficulties experienced by third-semester EFL students at Tadulako University in producing the English interdental fricative sounds /θ/ and /ð/. The objectives of this study are to identify the most difficult fricative sounds and to determine the factors influencing these difficulties. This study employed a descriptive quantitative design involving 16 students of the English Education Study Program. The data were collected through a pronunciation test and a questionnaire. The pronunciation test required students to read 20 words containing /θ/ and /ð/, and the results were analyzed using descriptive statistics. The questionnaire data were analyzed using mean scores and percentage distribution. The findings reveal that /θ/ was the most problematic sound, frequently substituted with /t/, while /ð/ was less problematic and occasionally replaced with /d/. The results also show that 9 students achieved excellent scores, while others showed varying levels of difficulty. In terms of influencing factors, mother tongue influence and psychological factors were identified as the most dominant, each contributing 21.3% to pronunciation difficulties. These findings indicate that first language interference and learners’ anxiety play significant roles in students’ pronunciation performance.